Spain: Information from the I.F.T.U. : inter-departmental correspondence (copy) - Carthy, A. E.
030-0190-001 A.E. CARTHY International Mr. H.V. TEWSON 29th April, 1938. SPAIN INFORMATION FROM THE I.F.T.U What is the position with regard to food since January? The position is very bad at the moment. The I.F.T.U. have just received an enquiry from Santiago, the officer of the Spanish Committee of the International Solidarity Fund, begging supplies of dried fish, meat (of which supplies are exhausted), and peas, for all of which the need is critical. From 1.1.38 to date: 1,491,112.50 French francs. What are the I.F.T.U. proposing to do with regard to relief in Spain in the future, and where is the need the greatest? They are continuing to work through the Spanish Committee of the International Solidarity Fund, which arranges for one or two persons to be at Valencia, and all consignments can be sent to Santiago at Valencia. With regard to greatest need, the situation before the rebels cut the road from Barcelona to Valencia was that the greatest need was in Barcelona, because the South has rice available. They would have to examine the situation, and could reply in a couple of days. Do the I.F.T.U. think it would be better if food were sent from France, rather then that we should ship direct from here? As far as Valencia is concerned, it would be better if supplies were sent in British bottoms, from England, because of the greater security, and the greater certainty that they will arrive at Valencia. As far as Barcelona is concerned, the I.F.T.U. would prefer to do it from Paris, because they can make quicker arrangements. It would mean a considerable saving in time if, for consignments going from France, the I.F.T.U. could be supplied with the money to make the purchases. What is the approximate cost paid by the I.F.T.U. for 2-ton lorries? Will write giving the information. AC/467. 292/946/30/190